Zoning Erosion Hazard and Sediment Estimation in Cham Gardalan basin (Ilam province) using the Revised Universal Soil Erosion Equation (RUSLE) - Saleh Arekhi; Shahram Barani; Somia Emadaddian (مخاطرات محیط طبیعی)
Soil erosion is one of the environmental problems that pose a threat to natural resources, agriculture and the environment. Quantitative assessment of erosion and sediment using erosion and sediment estimation models is one of the solutions through which erosion and sediment can be controlled to some extent and its amount minimized. In the present study, the aim is to predict the annual soil loss potential and sediment load. To predict these cases, the Revised Universal Soil Loss Equation (RUSLE) has been used in the context of the GIS. The amount of annual rainfall erosivity factor was calculated using 22-year monthly rainfall data at 18 stations around the basin. Its spatial variations were then estimated using conventional kriging. Soil erodibility index was obtained from soil map, which was prepared using field survey and remote sensing data. The topographic factor was extracted from the digital elevation model with a spatial resolution of 30 m. The annual vegetation factor was also estimated from remote sensing data. Since soil protection operations are insignificant in the study basin, the amount of soil protection factor was considered 1 throughout Basin. In this study, the mean values ​​of R, K, LS, C and P factors were equal to 264 MJ mm ha-1h-1y-1, 0.35 Mg ha h ha-1MJ-1mm-1, 2.00, 0.51 and 1. The average annual sediment yield in the study basin was estimated to be 16.137 th-1y-1, which was close to the value obtained from the sediment measuring station of the basin outlet (16.58 tons per hectare per year). The results of the erosion map in this model show that most erosion is located in the western and middle part of the basin. Because this region is composed of unstable formations and prone to erosion. The steep slope of the region, in addition to rainfall and land use change in this area, has faced many areas with soil erosion crisis. According to the results, the largest area of ​​the basin is related to the very low, low and medium erosion class, which is generally distributed throughout the basin, and the lowest basin area is in the high to very high erosion class (20%). Due to the fact that 20% of the study basin is in the high to very high erosion class, the need for protection measures in these areas is mandatory. The results of this study also showed that LS factor with a correlation coefficient of 0.81 had the greatest effect on estimating annual soil erosion by RUSLE model. This study proved the effectiveness of RS and GIS for quantitative estimation of soil erosion amounts, sediment yield and also erosion management.